School and Non-School Mathematical Knowledge: Building Cultural Dialogues (Interdisciplinary Studies Journal, 2024)
This study is part of a thesis investigation in the Postgraduate Program in Education in Science and Mathematics at the Federal University of Pará. It is a qualitative ethnographic research, whose objective is to identify traditional mathematical knowledge from the cultural context of an Amazonian fishing community (non-school-based) and associate it with curricular mathematical knowledge (school-based). The research was conducted in the Fishermen's Village of Bragança-PA, based on experiences in trap fishing. The theoretical foundation is centered on ethnomathematics, based on authors such as D'Ambrosio (2019) and Costa and Ghedin (2021), among others. Six different non-school-based mathematical knowledges were identified, which were associated with 16 different school-based mathematical knowledges, and these, in turn, generated 17 relationships between them. These relationships emerge as an opportunity to contextualize traditional knowledge in the school curriculum, gaining special significance when applied in educational institutions within fishing communities.
Keywords: Curriculum; Ethnomathematics; Mathematics; Traditional Knowledge